2014
DOI: 10.1111/bjd.13287
|View full text |Cite
|
Sign up to set email alerts
|

Hypotrichosis associated with capillary malformation-arteriovenous malformation syndrome

Abstract: Red punctate spots with pale halos or small telangiectasias are frequent findings in CM-AVM syndrome. Hypotrichosis on the CMs suggests that RASA1 gene mutations could be involved in the hair follicle proliferation and cell cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Some of them have a blanched perilesional halo, which has been related to vascular steal (high flow with direct arteriovenous shunting) 10,12,13 . Hypotrichosis has been occasionally described as well 22 . The term ‘rhodoid nevus’ has been proposed but not widely accepted as an alternative name for these lesions, 23 and ‘rhodoid naevus syndrome’ for CM‐AVM syndrome 17 …”
Section: Discussionmentioning
confidence: 99%
“…Some of them have a blanched perilesional halo, which has been related to vascular steal (high flow with direct arteriovenous shunting) 10,12,13 . Hypotrichosis has been occasionally described as well 22 . The term ‘rhodoid nevus’ has been proposed but not widely accepted as an alternative name for these lesions, 23 and ‘rhodoid naevus syndrome’ for CM‐AVM syndrome 17 …”
Section: Discussionmentioning
confidence: 99%
“…The published prevalence rate of CM‐AVM is 0.85–1 per 100 000 population, 2,8 but in our series, we estimated a prevalence of 0.13 cases per 100 000 (64 patients from a population of 46 million). This lower figure is probably an underestimate because patients with mild symtoms may not consult a physician 2,14 …”
Section: Discussionmentioning
confidence: 57%
“…CM-AVM is characterized by multiple familial pinkish macules (PMs) 7 that can exhibit a brownish hue, by a perilesional whitish halo that occurs in half of the lesions, 3 and by hypotrichosis. 8 These PMs are considered to be cutaneous micro-AVMs. 4,9,10 Onethird of patients have a fast-flow vascular malformation (FFVM) in the skin, muscle, bone, brain or spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Martin-Santiago et al (8), who found lower hair density on CMs than on the adjacent skin, recently reported dermoscopic findings in CM-AVM syndrome. We were unable to confirm this finding in our patients, who all had low hair density, and the dermoscopic features we found in CMs were previously undescribed.…”
Section: Discussionmentioning
confidence: 97%
“…They may be surrounded by a typical vasoconstriction halo and are often the first and only sign in children . Dermoscopy is a simple, noninvasive clinical and diagnostic tool for enhanced evaluation of a wide variety of cutaneous tumoral or nontumoral vascular disorders, but dermoscopic features of CMs in this syndrome have rarely been studied . Herein we report dermoscopic characteristics of CMs in four individuals with CM‐AVM syndrome with a typical combination of vascular and pigmentary patterns.…”
mentioning
confidence: 95%